2017
DOI: 10.12973/iji.2017.10116a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pragmatic Competence in Nigerian Undergraduates’ Language Errors within Descriptive ESL Writing

Abstract: This study investigates the level of pragmatic competence for ESL writing skills among Nigerian undergraduates. Methodologically, it adopts descriptive research design within the explanatory framework of the QUAN-Qual model. The instruments used are descriptive essay text and focus group interview questions. In writing the descriptive essays, a total of 402 undergraduates' participated through convenience sampling. Quantitatively, an independent samples t-test was carried out. The results indicated the females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
3
5
3
Order By: Relevance
“…The errors made by students in this area include errors in punctuation and capitalization. These findings contradict with the results by Muhammad and Subadrah (2017) that indicated that female students in Nigeria commit more errors in mechanics than their male counterparts, but supports the findings by Tesfaye (2004) that male students made more errors in punctuation and capitalization.…”
Section: Research Question 2b (Rq 2b)contrasting
confidence: 93%
See 3 more Smart Citations
“…The errors made by students in this area include errors in punctuation and capitalization. These findings contradict with the results by Muhammad and Subadrah (2017) that indicated that female students in Nigeria commit more errors in mechanics than their male counterparts, but supports the findings by Tesfaye (2004) that male students made more errors in punctuation and capitalization.…”
Section: Research Question 2b (Rq 2b)contrasting
confidence: 93%
“…Errors in this area are found in word form, articles, prepositions and conjunctions. These findings conform to the findings by Furtina et al (2016) that female students made less grammatical errors than male students in writing, but contradict the findings by Muhammad and Subadrah (2017) that female students in Nigeria made more grammatical errors than their male counterparts.…”
Section: Research Question 2c (Rq 2c)supporting
confidence: 89%
See 2 more Smart Citations
“…In fact, it was found that there were still many problems students experienced in academic writing activities. Muhammad said the majority of the learners' face significant challenges in the areas of mechanical, grammatical, and sentence formations [12]. In line with this opinion, Akhadiah [13] says that many students are difficult in using written language.…”
Section: Introductionmentioning
confidence: 97%